Damage State of Non-Engineered Residential Buildings Owing to Earthquakes: A Case Study in Pacitan Regency, Indonesia - Kristiawan Stefanus Adi; Safarizki Hendramawat Aski; Purwanto Edy; Sangadji Senot; Trisnawan Ahda Dinansya; Nugroho Tonny Setyo (Civil and Environmental Engineering, 2024)
The Pacitan Regency of Indonesia is located in an area of high seismic activities. Regrettably, field surveys held in Pacitan Regency, Indonesia have revealed the prevalence of low-income housing structures that do not meet the engineering standards and are vulnerable to damage during earthquakes. The seismic evaluation of these buildings is urgently required. This study proposes realistic damage state limit values for the seismic damage evaluation of non-engineered buildings. For this purpose, an incremental dynamic analysis was conducted on a sample of non-engineered buildings in Pacitan to evaluate their probable seismic damage. As a result, curves showing the dynamic pushover responses of buildings to various input earthquakes were plotted. These curves were then summarized as three-linear curves, providing a single value for the average response of the structure. Based on this simplified curve, a more realistic damage-state limit for non-engineered structures are proposed. The damage levels of slight (DS1), moderate (DS2), extensive (DS3), and complete (DS4) were determined using the drift ratio at the linear elastic limit, midway point between the linear elastic and yield limits, yield state, and 80% rupture limit, respectively.